Students’ Exposure to Generative AI Models and Its Influence on English Writing Proficiency - Renacido, John Marvin D.; Teodosio, Jemuel; Dumalaog, Rodje D.; Repayo, Benedicta D.; Biray, Ersyl T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The predominance of Generative Artificial Intelligence (Gen AI) models on the web poses significant effects on the learning habits of the students at a state university due to its convenience in terms of access, grammar correction, paraphrasing text, and generating ideas. As a result, these features of Gen AI models have been the cause of the dissented researchers’ conclusion, and teachers raise concerns regarding their possible disadvantages to the students. Several researchers have shown the advantages and disadvantages of using Gen AI models in the academic endeavors of students. Hence, this study determined the relationship between exposure to Gen AI tools and the English writing proficiency of freshmen students specializing in the English language under an education program in a state university in the northern part of Panay Island in the Philippines. The descriptive correlation design was utilized to examine the relationship between two variables. A validated researcher-made questionnaire and essay writing performance test were used to gather the students’ profiles and to measure their English writing proficiency, respectively. Results revealed that the majority of the freshmen education students specializing in English language were female, most have used the Gen AI tool Quillbot but have low exposure to other Gen AI tools, and a moderately satisfactory rating in their English writing proficiency. It further established that the English writing proficiency has no or negligible relationship with their exposure to Gen AI tools.